Extracurricular and Intracurricular at Modern Islamic Boarding School Darul Hikmah Islamic Education Park - Jihan Andini; Nuha Muadzah Rana; Rifky Amardiaz (Yayasan Zia Salsabila, 2022)
The background of this study is to demonstrate the effects of extracurricular activities that enable students of Darul Hikmah TPI Islamic Boarding School to discover their talents and interests through extracurricular activities. The purpose of this study was to analyze extra-curricular activities at the Darul Hikma Islamic Boarding School and to analyze what methods were used to participate in extra-curricular activities. This type of research uses descriptive qualitative research. The research topics used are OSPIDAH administrators, specifically the artists section responsible for the extracurricular part of the Darul Hikma of the Islamic Borders.